The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1016/0304-3959(94)00170-j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketamine, an NMDA receptor inhibitor, in acute and chronic orofacial pain

Abstract: We examined the analgesic effect of racemic ketamine and its 2 enantiomers in 16 female patients (age: 20-29 years) suffering acute pain after oral surgery and in 7 female patients (age: 42-79 years) suffering chronic neuropathic orofacial pain. All 3 forms of ketamine consistently relieved postoperative pain, (S)-ketamine being 4 times more potent than (R)-ketamine. The analgesic effect was maximal 5 min after i.m. injection and lasted for about 30 min. The 7 patients with neuropathic pain received ketamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(139 citation statements)
references
References 13 publications
5
128
1
4
Order By: Relevance
“…In various studies done by Satilmiş et al [32], Garip et al [33], Gupta et al [36] ketamine has shown to reduce postoperative pain and swelling in patients undergoing surgical removal of third molars and also provide a comfortable procedure for the surgeon and patient. But in contrast Lebrun et al [35] concluded that there was no benefit to pre-emptive administration of ketamine 300 lg/ kg iv whether administered pre-or postoperatively after assessing the effect on 84 patients scheduled for third molar surgical removal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In various studies done by Satilmiş et al [32], Garip et al [33], Gupta et al [36] ketamine has shown to reduce postoperative pain and swelling in patients undergoing surgical removal of third molars and also provide a comfortable procedure for the surgeon and patient. But in contrast Lebrun et al [35] concluded that there was no benefit to pre-emptive administration of ketamine 300 lg/ kg iv whether administered pre-or postoperatively after assessing the effect on 84 patients scheduled for third molar surgical removal.…”
Section: Discussionmentioning
confidence: 99%
“…Recently ketamine has been used in oral and maxillofacial surgical practice as well [14,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In man, S(+)Ketamine has an anaesthetic-analgesic effect two to four times greater than racemic ketamine (White et al 1985, Mathisen et al 1995, Lauretti et al 2000, and its hyptonic effect is more potent than that of the R(-) isomer (Terra et al 1999), witch allows the use of lower doses of S(+) ketamine when compared to racemic ketamine. Rossetti et al (2008) observed in stallions undergoing castration, a higher analgesic effect of S(+)-ketamine, which was represented by a more stable physiologic parameters during the procedure and also a lower anesthetic requirement.…”
Section: Discussionmentioning
confidence: 99%
“…In man, S(+)Ketamine has an anaesthetic-analgesic effect two to four times greater than racemic ketamine (White et al 1985;Mathisen et al 1995;Lauretti et al 2000), and its hyptonic effect is more potent than that of the R(-) isomer (Terra et al 1999), allowing the use of lower doses of S(+) ketamine compared to racemic ketamine.…”
Section: Introductionmentioning
confidence: 99%